INSTITUTIONAL QUALITY AND FINANCIAL CRIMES IN WEST AFRICA - Muhammed Lawal SUBAIR; Ahmed Ambal ISIAKA; Majeed Ajibola IBRAHIM; O.A. OYENIYI (Malete Journal of Accounting and Finance)
The high level of financial crimes in West African countries have negatively impacted upon the smooth functioning of institutions, thus leading to the disintegration of social structures, negative economic expansion, decline in both domestic and international investment, and a worsening of the state of law and order throughout the region. In the light of this, the study investigated the relationship between financial crime and institutional quality in West African nations. Two hypotheses were constructed to guide the inquiry using estimation panel data from Multiple Regression Analysis in 16 West African nations from 2013 to 2023. Basel Anti Money Laundering and the World Bank Governance Indicator were used to gather data for the study from secondary sources. Strong evidence of a negative regression coefficient between political stability and government performance in relation to financial crime is provided by the results, which show -0.387 and -1.938 with p-values of 0.021 and 0.001, respectively. The study concluded that poor quality of institutions has been contributing to higher crimes statistics in West Africa countries. Therefore, the study recommended that national governments should focus on improving the political stability and government effectiveness to reduce crime in West Africa countries.